Impacts of Tourism on Locals' Lives and Attitudes - Vuokila, Niko Lauri Johannes (2020)
The aim of this thesis was to research the positive and negative impacts of tourism on local people’s lives in Rovaniemi and Kemi and the local people’s attitudes towards tourism and its development in their cities. Tourism has been rapidly growing in Lapland during the recent years, thus making research about the subject necessary. The thesis was commissioned by the arctic travel ecosystem for Lapland -project. The contact person was the project manager Kristian Sievers. A literature review acts as the basis for this paper, explaining main concepts of impacts of tourism. The impacts were categorized into economic, sociocultural and environmental impacts. Then possible positive and negative impacts of tourism were identified. Sharing economy, more precisely Airbnb in this study, was also included in the research due to its possible economic and sociocultural impacts. Airbnb has been growing in Rovaniemi while dividing opinions about it greatly For the research methodology a quantitative approach was chosen and the research was conducted as a survey utilizing a five-point Likert scale. The survey was distributed online through the social media platform Facebook. The survey gathered 297 responses from Rovaniemi and 154 from Kemi. Tourism has had more impacts to locals’ lives in Rovaniemi, where tourism growth has been more substantial. Both positive and negative impacts were identified in all sectors, but Kemi experienced almost all impacts in lesser extent. The most significant economic impacts found were the increases in prices of services and the cost of living Rovaniemi. However, tourism has also made the city feel healthier and it has brought more job opportunities for the locals. According to the respondents, tourism has mostly not affected their quality of life negatively, but environmental impacts have been notable to some extent in Rovaniemi. Residents of Kemi reported no environmental impacts. Furthermore, residents were mostly positive about tourism and its development in both cities. Opinnäytetyön tavoitteena oli tutkia matkailun positiivisia ja negatiivisia vaikutuksia paikallisten asukkaiden elämään ja asenteisiin matkailua kohtaan Rovaniemellä ja Kemissä. Viime vuosina matkailun kasvu on ollut Lapissa suurta, joten tutkimus oli aiheellinen. Opinnäytetyön toimeksiantajana toimi Lapin arktinen matkailuekosysteemi -hanke ja yhteishenkilönä toimi projektipäällikkö Kristian Sievers. Matkailun vaikutukset lajiteltiin ekonomisiin, sosiokulttuurillisiin ja ympäristöllisiin ulottuvuuksiin. Mahdollisia positiivisia ja negatiivisia vaikutuksia tutkittiin aikaisemman kirjallisuuden perusteella. Myös jakamistaloutta, tässä tutkimuksessa Airbnb:tä tutkittiin sen mahdollisten ekonomisten ja sosiokulttuurillisten vaikutusten takia. Airbnb kasvanut Rovaniemellä ja se on ilmiönä aiheuttanut paljon keskustelua ja jakanut asukkaiden mielipiteitä. Tutkimusmetodiksi valittiin määrällinen tutkimus, ja se toteutettiin kyselyn avulla. Kyselyssä käytettiin viisiportaista Likert-asteikkoa. Vastaajajoukko tavoitettiin Facebookin paikallisista asukkaista koostuvista ryhmistä. Vastauksia saatiin Rovaniemeltä 297 ja Kemistä 154. Tutkimuksen perusteella voidaan päätellä, että matkailu vaikutti paikallisten elämään enemmän Rovaniemellä, jossa kasvu on ollut suurempaa. Positiivisia ja negatiivisia vaikutuksia löydettiin kaikilta aihealueilta, mutta Kemissä lähes kaikki vaikutukset olivat vaikutukseltaan vähäisempiä. Merkittävimmät löydetyt ekonomiset vaikutukset olivat elinkustannusten ja paikallisten palvelujen hintojen nousu, mutta matkailu teki kaupungeista myös elinvoimaisempia. Vastaajien mukaan matkailu ei ole vaikuttanut heidän elämänlaatuunsa negatiivisesti. Rovaniemellä on ollut negatiivisia vaikutuksia ympäristöön, mutta Kemissä vaikutuksia ei juurikaan esiintynyt. Molemmissa kaupungeissa vastaajien asenteet matkailua kohtaan olivat jokseenkin positiivisia.